Hydrolysed Collagen from Sheepskins as a Source of Functional Peptides with Antioxidant Activity - León-López, Arely (Int J Mol Sci, 2019)
The extraction and enzymatic hydrolysis of collagen from sheepskins at different times of hydrolysis (0, 10, 15, 20, 30 min, 1, 2, 3 and 4 h) were investigated in terms of amino acid content (hydroxyproline), isoelectric point, molecular weight (Mw) by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) method, viscosity, Fourier-transform infrared (FTIR) spectroscopy, antioxidant capacity by 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays, thermal properties (Differential Scanning Calorimetry) and morphology by scanning electron microscopy (SEM) technique. The kinetics of hydrolysis showed an increase in the protein and hydroxyproline concentration as the hydrolysis time increased to 4 h. FTIR spectra allowed us to identify the functional groups of hydrolysed collagen (HC) in the amide I region for collagen. The isoelectric point shifted to lower values compared to the native collagen precursor. The change in molecular weight and viscosity from time 0 min to 4 h promoted important antioxidant activity in the resulting HC. The lower the Mw, the greater the ability to donate an electron or hydrogen to stabilize radicals. From the SEM images it was evident that HC after 2 h had a porous and spongy structure. These results suggest that HC could be a good alternative to replace HC from typical sources like pigs, cows and fish.